The Role of Plasmids in the Multiple Antibiotic Resistance Transfer in ESBLs-Producing Escherichia coli Isolated From Wastewater Treatment Plants - Li, Qing; Chang, Weishan; Zhang, Hongna; Hu, Dong; Wang, Xuepeng (Frontiers in Microbiology, 2019)
We compared the diversity of extended-spectrum beta-lactamases (ESBLs) producing Escherichia coli (E. coli) in wastewater of a municipal wastewater treatment plant (WTP) by analyzing multidrug-resistant phenotypes with genotypes, and to investigate the multidrug-resistant transfer mechanism of plasmid by comparing the multidrug-gene linked transfer using conjugative test, and by analyzing one plasmid full-length DNA sequence. The results showed that 50 isolates of ESBLs-producing E. coli were isolated from 80 wastewater samples at the rate of 62.5% (50/80), out of which, 35 transconjugants were obtained successfully with the multidrug-resistant transfer rate as high as 70.0% (35/50). Multidrug-resistance (3 or more antibiotics resistance in phenotypes and genotypes) were showed in all donor bacteria and transconjugants. Both donor bacteria and transconjugants were capable of resistant to 11 out of 15 kinds of antibiotics. Among them, drug resistance spectrum of transconjugants narrowed than donor bacteria at the rate of 94.29% (33/35) and broadened at the rate of 5.71% (2/35). However, the drug resistance pattern was changed compared with donor bacteria and transconjugants, one or several drugs resistance was lost and another drug resistance was added. PCR amplification results showed that the resistant genotypes decreased or remained unchanged when compared donor bacteria with transconjugants, the blaTEM and blaCTX-M genes were successfully transferred in all transconjugants, the blaSHV gene was successfully transferred at the rate as high as 94.29% (33/35). However, the qnrS gene was transferred at the rate as lower as 4.17% (1/24). In addition, the major resistance gene subtypes were blaTEM-1, blaSHV-11 and blaCTX-M-15 according to sequencing and Blast comparison. Plasmid wwA8 is a closed-loop DNA molecule with 83157 bp, contains 45 predicted genes including three drug resistance genes, blaCTX-M-15, blaTEM-1 and qnrS1, which can be transferred with E. coli in vitro. This study shows that different resistance genes may be located on different plasmids. E. coli isolated from wastewater was capable of resistance genes transfer, and produce drug resistance phenotypes. The plasmids in E. coli play an important role in the multidrug-resistant linked transfer.